2010
DOI: 10.1088/0004-637x/723/1/300
|View full text |Cite
|
Sign up to set email alerts
|

THREE-DIMENSIONAL SOLARWINDMODELING FROM THE SUN TO EARTH BY A SIP-CESE MHD MODEL WITH A SIX-COMPONENT GRID

Abstract: The objective of this paper is to explore the application of a six-component overset grid to solar wind simulation with a three-dimensional (3D) Solar-InterPlanetary Conservation Element/Solution Element MHD model. The essential focus of our numerical model is devoted to dealing with: (1) the singularity and mesh convergence near the poles via the use of the six-component grid system, (2) the ∇ · B constraint error via an easy-to-use cleaning procedure by a fast multigrid Poisson solver, (3) the Courant-Friedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
144
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(156 citation statements)
references
References 114 publications
3
144
0
1
Order By: Relevance
“…The Alfvén wave pressure prediction is determined along the PFSS magnetic field, while the final obtained field line topology of the solar wind model departs from this PFSS field so that the velocity profile at 1 AU is likely to be different from the WSA predicted values. Actually, some studies found the WSA model yields higher solar wind speed at the source surface than the MHD model does (Feng et al 2010). To overcome this issue, we may need a self-consistent method to treat the inner boundary for Alfvén wave energy.…”
Section: Discussionmentioning
confidence: 99%
“…The Alfvén wave pressure prediction is determined along the PFSS magnetic field, while the final obtained field line topology of the solar wind model departs from this PFSS field so that the velocity profile at 1 AU is likely to be different from the WSA predicted values. Actually, some studies found the WSA model yields higher solar wind speed at the source surface than the MHD model does (Feng et al 2010). To overcome this issue, we may need a self-consistent method to treat the inner boundary for Alfvén wave energy.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the 3D SIP-CESE MHD model were described in Feng, Zhou, and Wu (2007) and Feng et al (2010). In this section only the basic features and modifications specific to this study are given.…”
Section: The 3d Sip-cese Mhd Modelmentioning
confidence: 99%
“…In the present study, we will use the three-dimensional (3D) SolarInterPlanetary Conservation Element/Solution Element (SIP-CESE) Magnetohydrodynamic (MHD) model (Feng, Zhou, and Wu, 2007;Feng et al, 2010) to numerically investigate the peculiarities of the current minimum and to explore their relationship with the polar magnetic fields on the solar surface. In order to achieve this, we have chosen CR 2070 as the simulation time interval and we will compare the numerical results with observations from multiple satellites, such as SOHO, Ulysses, Solar Terrestrial Relations Observatory (STEREO, Kaiser et al, 2008), Wind (Lepping et al, 1995) and ACE.…”
Section: Introductionmentioning
confidence: 99%
“…These, however, require some form of interpolation scheme to establish a seamless connection between the sub-grids, which usually destroys the conservative properties of the code within the interpolation region. For applications of these grids to 3-D solar wind modeling see Feng et al (2010Feng et al ( , 2011. Cartesian coordinates, which do not present such difficulties, remain popular among CME modelers for exactly this reason, although the implementation of spherical boundaries like the photosphere then either requires some form of weighted interpolation procedure (e.g.…”
Section: Numerical Mhd Propagation Modelsmentioning
confidence: 99%